Baccalaureates or Burdens? Complicating "Reasonable Accommodations" for American College Students with Disabilities - Emily Krebs (Disability Studies Quarterly, 2019)
This paper examines the controversy surrounding American college students' use of disability accommodations, a process many find unfair or undue, in two ways: (1) by critically unpacking the processes for obtaining accommodations to highlight intersectional issues of who has—or is barred from—access to such services; and (2) by using a rhetorical lens to analyze how the term "accommodation" influences perceptions of disabled students. By combining these processual and rhetorical approaches, this work uncovers significant issues regarding how university students with disabilities are treated on college campuses. Such research is important because disabled individuals are less than half as likely as their nondisabled peers to earn college degrees. Thus, despite ADA laws and pushes for inclusivity and diversity on college campuses, the American higher education system continues to fail a significant part of the nation's population.
Keywords: accommodations; Americans with Disabilities Act; bioculturalism; crip theory; disability studies